Regional body fat depots differently affect bone microarchitecture in postmenopausal Korean women. Issue 3 (March 2016) - Kim, J.; Choi, H.; Ku, E.; Hong, A.; Kim, K.; Kim, S.; Cho, N.; Shin, C.
Abstract Summary In a prospective community-based cohort study, we investigated the relationship between trabecular bone score (TBS) and regional fat depots in 1474 Korean postmenopausal women. TBS was positively related with subcutaneous fat and negatively related with visceral fat. Introduction The effect of fat distribution (visceral/subcutaneous) on bone quality or microarchitecture has rarely been investigated due to measurement difficulty. We aimed to investigate the relationship between TBS reflecting bone microarchitecture and regional fat depots in Korean women. Methods Cross-sectional data evaluation was made from subjects participating in an ongoing prospective community-based cohort study since 2001. A total of 1474 postmenopausal women in the Ansung cohort were analyzed. Regional body fat mass, bone mineral density (BMD) at the lumbar spine, and total hip and lumbar spine TBS were measured by dual energy X-ray absorptiometry (DXA). Results In an age-adjusted partial correlation analysis, TBS was not associated with total fat mass, but negatively associated with trunk fat mass. However, TBS was positively related with leg (r  = 0.102, P  < 0.05) and gynoid fat mass (r =  0.086, P  < 0.05) and negatively related with android fat mass (r  = −0.106;P  < 0.05). In linear regression models controlling age, BMI, and physical activity, android fat was inversely associated with TBS (β  = −0.595, P  < 0.001), whereas gynoid fat was positively associated with TBS (β  = 0.216, P  < 0.001). Lumbar spine and total hip BMDs revealed positive associations with total and all regional fat depots regardless of fat distribution. Conclusion Our findings suggest that relatively large visceral fat and small subcutaneous fat may have a detrimental effect on TBS, a bone microarchitecture index.